Molecular Dynamics Simulations of Micellization of Alkyl Ethoxylate - Yogesh, R.; Behera, R.N. (Asian Journal of Chemistry, 2012)
Micellization of the non-ionic surfactants alkyl ethoxylate (poly oxyethylene alcohols C12H25(OC2H4)4OH) has been studied using atomistic explicit-solvent molecular dynamics simulations. The simulations were carried out in a wide range of surfactant concentrations (ca. 0.05 M-0.9 M) above the critical micelle concentration. An analysis of the number of cluster formed with time showed that all the system studied aggregated into a small number of clusters rapidly within about 200 ps and then the clusters aggregated into a spherical type micelle (in most of the cases) in about 1 ns. Various system properties are analyzed to predict trends with variation of concentration, chain lengths, etc. It is observed that variation of chain lengths (both polar as well as non-polar part) has a significant influence in the system properties. The implicit-solvent molecular dynamics study of the same system with dielectric constants 80 and 30 indicated that implicit-solvent model is not able to capture the phenomena of micellization properly.